TRANSLATION PROCEDURES ON TOURISM BROCHURE FROM INDONESIAN INTO ENGLISH - Tarisa Fingky (LPPM Universitas Dhyana Pura, 2023)
This study aims to analyze the translation procedures found on Tourism Brochure. Thequalitative descriptive method is used in this study to analyze the data. The source of the datawas a tourism brochure of Borobudur Temple English-Indonesian version. Data were collectedon brochure from page 1-2. Theory of Newmark (1988) regarding of translation procedureswas used to analyze the data. The results show there are 7 procedures found in TourismBrochure, namely transposition, modulation, adaption, transference, addition, descriptiveequivalent, naturalization, reduction. Based on research that has been carried out, found 8 outof 15 translation procedures. The most commonly used translation found in this study aretransposition, naturalization and transference with a total of 21 data points.